COLLABORATIVE LEARNING AND SCIENTIFIC WRITING IN HYBRID EDUCATION: TOOLS, STRATEGIES AND CHALLENGES - Guenani Fatma; Lazhar Benaissa (International Journal of Innovative Technologies in Social Science, 2025)
This study explores the impact of hybrid education on the development of scientific writing skills and the construction of collaborative learning communities. By combining face-to-face and digital tools, hybrid education transforms teaching practices and promotes an interactive and flexible approach to learning. The integration of information and communication technologies (ICT) allows for more personalized coaching, increased collaboration between students and teachers, as well as continuous evaluation of academic outputs. However, despite its many advantages, this model poses challenges in terms of student engagement, teacher training and adaptation to new learning methodologies. Through an in-depth analysis of hybrid teaching models, digital tools and collaborative learning strategies, This study highlights best practices and offers recommendations to optimize the effectiveness of hybrid teaching in the academic setting.